IMPACT OF POSTURE AND RECOVERY METHODS ON SPORTS INJURIES - Liu,Tao (2022)
ABSTRACT Introduction Exercise methods with incorrect posture or inadequate repetitive movements may cause irreversible long-term body damage. There is a growing interest in ergonomics in martial arts, but taekwondo lacks studies. Objective Evaluate the postural ergonomics impact on injuries and rehabilitation in taekwondo athletes. Methods 13 taekwondo team members from a sports academy had their posture and injury characteristics evaluated. Research methods, experimental and mathematical statistics investigated the athletes’ postural and body diagnosis, confronting the information with their injury history, pain, and injury duration. Results Nine athletes suffered injuries and pain in the pelvic girdle and ankle joints; the odds are 69.23%, pelvic girdle and ankle joints have the highest frequency of injuries, followed by knee injuries (46.15%), and foot joints (30.77%). Injuries to the thigh, wrist, and shoulder joints were detected in 23.08% of athletes. Conclusions The results of this study indicate postural dysfunctions can be corrected with motor function evaluation and early rehabilitation based on ergonomic sports posture. Evidence Level II; Therapeutic Studies - Investigating the result.